Ethics as a Dependent Variable in Individual and Organisational Decision Making - Lovell, Alan (Journal of business ethics, 2002)
This paper draws upon a recently completed research study of the responses of accountants and HR professionals to actual issues at work that had posed them ethical qualms. The study sought to get beyond ethical reasoning about hypothetical scenarios and to address issues of actual behaviour, focusing upon the interviewees explanations of these behaviours. In general terms there was an observable difference between the attitudes and behaviours of accountants and HR professions, but not in the simple, stereotypical sense. The concerns expressed by the interviewees when calculating their chosen courses of action in a given situation, reflected grave concerns for their current and future employment prospects, if they were to raise their concerns, either within their employing organisation, or beyond. The problems of whistleblowers are well documented, but at a time when corporate governance issues occupy the attention of financial markets and corporate boards around the world, and national governments are introducing new laws to ostensibly provide enhanced protection for whistleblowers, the evidence of this study is that moral agency remains at best an aspiration, and at worst a chimera.